THSD7B promotes tumor progression and is associated with prognosis in gastric adenocarcinoma - Xinying Quan; Wei Cheng; Yao Pu; Hong Deng (PLoS ONE, 2026)
THSD7B (thrombospondin type-1 domain-containing 7B) has been implicated in several malignancies; however, its role in gastric adenocarcinoma remains unclear. This study aimed to investigate the expression pattern, clinical significance, and biological function of THSD7B in gastric adenocarcinoma. Public datasets from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were analyzed to evaluate THSD7B expression and its association with clinical outcomes. Functional enrichment analysis was performed to explore potential biological processes. In vitro assays, including cell proliferation, colony formation, wound healing, and Transwell invasion, were conducted following THSD7B knockdown or overexpression in gastric cancer cell lines. In addition, a xenograft model was established to assess tumor growth in vivo. THSD7B expression was significantly elevated in gastric adenocarcinoma tissues compared with normal controls and was associated with patient survival. Functional analyses suggested that THSD7B-related genes were mainly enriched in cell adhesion and cytoskeleton-associated processes. In vitro experiments showed that THSD7B knockdown suppressed cell proliferation, migration, and invasion, whereas overexpression produced the opposite effects. Consistent with these findings, THSD7B modulation was accompanied by alterations in adhesion-related signaling molecules and phenotype-associated protein expression. In vivo, THSD7B promoted tumor growth in xenograft models. In conclusion, THSD7B is associated with tumor progression and clinical outcomes in gastric adenocarcinoma and may be involved in the regulation of cell motility-related processes. These findings suggest that THSD7B may serve as a potential biomarker in gastric cancer.